(untitled) (International Journal of Engineering and Computer Science, 2017)
Power quality is a major issue of loads in the distribution system used in industrial and domestical appliances. In this work, we proposed a modified solid state transformer system using statcom to improve the power quality of loads in the distribution system. The proposed model is used to eliminate voltage sag, and swell. The matrix converter is adopted in the proposed design of modified solid state transformer to reduce the power loss. The control strategy of matrix converter is done by sinusoidal pulse width modulation techniques. In addition to this, harmonics are reduced by using vector proportional integral controller. The simulation is done in MATLAB/SIMULINK software, the several case studies are carried out and the simulation results shows that the proposed system has better voltage regulation than that of conventional system.